2020
DOI: 10.5664/jcsm.8752
|View full text |Cite
|
Sign up to set email alerts
|

Positional obstructive sleep apnea within a large multicenter French cohort: prevalence, characteristics, and treatment outcomes

Abstract: Study Objectives: To assess, in a large cohort of patients with obstructive sleep apnea, the factors that are independently associated with positional obstructive sleep apnea (POSA) and exclusive POSA (e-POSA) and determine their prevalence. The secondary objective was to evaluate the outcome of positive airway pressure (PAP) therapy for patients with POSA and e-POSA. Methods: This retrospective study included 6,437 patients with typical mild-to-severe OSA from the Pays de la Loire sleep cohort. Patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 53 publications
7
26
1
1
Order By: Relevance
“…for severe OSA. These results are in line with the results in the literature showing that Supine PP are mainly dominant in the less severe groups of patients with OSA 14 . Moreover, our findings on Supine PP and siOSA prevalence among OSA in MESA were also aligned with previous reports 6,14, Overall, up to 34.0% of all OSA individuals were siOSA, and by using positional therapy (PT) efficiently, they could resolve their OSA condition.…”
Section: Discussionsupporting
confidence: 92%
“…for severe OSA. These results are in line with the results in the literature showing that Supine PP are mainly dominant in the less severe groups of patients with OSA 14 . Moreover, our findings on Supine PP and siOSA prevalence among OSA in MESA were also aligned with previous reports 6,14, Overall, up to 34.0% of all OSA individuals were siOSA, and by using positional therapy (PT) efficiently, they could resolve their OSA condition.…”
Section: Discussionsupporting
confidence: 92%
“…These results, however, were markedly similar to findings observed in other cohorts. For example, the percentage of positional-OSA patients with a non-supine AHI events/h in the normal range in our cohort was equivalent to a recent study of 6,437 patients 6 . Women had lower pre-treatment overall, supine, and non-supine AHI values compared to men, and by-sex differences remained post-OAT 23,[31][32][33] .…”
Section: Discussionsupporting
confidence: 65%
“…Positive airway pressure is the standard of care for moderate to severe OSA, while OAT is recommended for those with mild to moderate OSA or intolerant of positive airway pressure 5 . Patients with mild to moderate OSA tend to be less symptomatic and less tolerant of positive airway pressure 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since higher BMI is associated with a higher degree of oropharyngeal lateral wall collapse [21], a decrease in BMI may lessen the severity of oropharyngeal lateral wall collapse, which in turn leads to a reduction in non-supine AHI. Second, a multicenter French cohort revealed that patients with positional OSA had a significantly lower likelihood of CPAP adherence and an increased risk of CPAP withdrawal as compared with non-positional OSA [22]. Previous studies utilized DISE to evaluate upper airway structural changes induced by CPAP titration [23,24].…”
Section: Discussionmentioning
confidence: 99%